DAMPAK KERUSUHAN 1997 TERHADAP INFRASTRUKTUR KOTA BANJARMASIN KALIMANTAN SELATAN - Aiga Herawati; Muhammad Rifky Ramadhani; Muhammad Ridho; Siti Nur Hikmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the impact of the 1997 Banjarmasin Riots on the state of infrastructure in the city of Banjarmasin. The study employs a historical method involving the stages of source collection, source criticism, interpretation, and historical writing. Data was obtained from various sources such as books, academic journals, archives, and newspaper articles relevant to the events. The research findings indicate that the 1997 riots caused significant damage to various city infrastructures, particularly to commercial centers, retail stores, commercial buildings, and public facilities. Additionally, the riots disrupted city services and the socio-economic activities of the community. The impact of this infrastructure damage was not merely physical but also affected the economic and social lives of the community over a considerable period. This study confirms that social conflict has multidimensional impacts encompassing social, economic, and physical aspects of the region. Therefore, social stability is a crucial factor in supporting the sustainability of urban development and preventing more extensive damage in thefuture.